2019
DOI: 10.3389/fpsyt.2019.00413
|View full text |Cite
|
Sign up to set email alerts
|

Level of Insight in Patients With Obsessive–Compulsive Disorder: An Exploratory Comparative Study Between Patients With “Good Insight” and “Poor Insight”

Abstract: Introduction: Insight may be defined as the ability to perceive and evaluate external reality and to separate it from its subjective aspects. It also refers to the ability to self-assess difficulties and personal qualities. Insight may be a predictor of success in the treatment of obsessive–compulsive disorder (OCD), so that individuals with poor insight tend to become refractory to treatment. The objective of this study is to investigate factors associated with poor insight in individuals with OCD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 92 publications
1
27
0
Order By: Relevance
“…Therefore, the present study supported the approval that insight level is a predictive factor on treatment adherence, and closely associated with the severity of clinical symptoms [32]. Many previous studies reported that OCD patients with poor insight show poor treatment adherence, more resistant symptoms, and more severe clinical symptoms [33]. Furthermore, duration of OCD was found to be related with lower insight level in several studies, and the insight level was also negatively correlated with the duration of the disorder in the present study [34].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the present study supported the approval that insight level is a predictive factor on treatment adherence, and closely associated with the severity of clinical symptoms [32]. Many previous studies reported that OCD patients with poor insight show poor treatment adherence, more resistant symptoms, and more severe clinical symptoms [33]. Furthermore, duration of OCD was found to be related with lower insight level in several studies, and the insight level was also negatively correlated with the duration of the disorder in the present study [34].…”
Section: Discussionsupporting
confidence: 88%
“…Agoraphobia, a fairly frequent disorder, was also statistically insignificant, with only four cases in the whole sample-two in the good-insight group and two in the control group. Although many authors claim that patients with poor insight display more comorbidities, recent studies have also failed to identify statistically relevant values of agoraphobia in OCD groups with good and poor insight [72], which suggests, for now, that the comorbidity of OCD with agoraphobia is not a research priority. As for depression, the percentage of patients suffering from this condition was higher in the poor-insight group (with p = 0.029, which coincides with the cut-off value, and a low effect size (0.25)).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the obsessional thoughts in OCD have been distinguished from the delusions and hallucinations in SCZ because of their lack of perceptual qualities and the high level of patients' insight. However, numerous studies have recently reconsidered this dichotomy by showing that patients with OCD have a wide range of insight levels [6,[48][49][50][51] and frequently described their obsessional thoughts as perceptual irritations [52][53][54][55]. Moreover, patients with SCZ with diagnosed hearing hallucinations often describe them as less loud than real voices or without perceptual qualities but merely as strange thoughts [56].…”
Section: Discussionmentioning
confidence: 99%